Willingness-to-pay for a booster dose of inactivated SARS-CoV-2 vaccine in Taizhou, China - Tao-Hsin Tung; Xiao-Qing Lin; Yan Chen; Mei-Xian Zhang; Jian-Sheng Zhu (Taylor & Francis Group, 2022)
This study was conducted to ascertain whether people in China would be willing to pay for an inactivated COVID-19 vaccine booster dose. An online survey estimating participants' willingness to pay (WTP) for a booster dose of COVID-19 vaccine was conducted in Taizhou, China. The participants received ane-mail or e-poster on WeChat. A total of 1576 subjects participated the survey. A total of 66.4% (1046/1576) of the respondents were willing to pay for a booster dose of COVID-19 vaccine for themselves. Using binary logistic regression analysis, the following factors were significantly related to a WTP for a booster dose of COVID-19 vaccine: 1) confidence in the safety of the COVID-19 vaccines (high vs. low, OR: 4.30, 95%CI: 1.61-11.43), 2) confidence in the preventive effectiveness of the COVID-19 vaccines against SARS-CoV-2 virus (moderate vs. little, OR: 1.76, 95%CI: 1.30-2.38; great vs. little, OR: 2.244, 95%CI: 1.62-3.12), and 3) COVID-19 vaccine hesitancy (unhesitant vs. very unhesitant, OR: 0.67, 95%CI: 0.45-1.02; hesitant vs. very unhesitant, OR: 0.29, 95%CI: 0.19-0.44; very hesitant vs. very unhesitant, OR: 0.09, 95%CI: 0.03-0.27). This study revealed that a moderate proportion of participants responded that they would be willing to pay for a booster dose of COVID-19 vaccine. These findings suggest the importance of a detailed assessment and a health education plan that better understands the population's risk perception as well as the potential health risks in China.